Exercise‐induced saphenous vein graft spasm prevented by stenting. Issue 6 (17th March 2017) - Boliek, William G.; Kereiakes, Dean J.; Chugh, Atul
Abstract : Recurrence of anginal symptoms following coronary artery bypass surgery is usually secondary to graft closure or progression of native vessel disease. The present case demonstrates severe exercise‐induced saphenous vein graft (SVG) spasm associated with transmural ischemia refractory to maximal vasodilator therapy. Symptoms resolved and exercise electrocardiography normalized following stenting of SVG regions demonstrating spasm. © 2017 Wiley Periodicals, Inc.